2021
DOI: 10.4103/jfmpc.jfmpc_2388_20
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin B12 status of patients with type 2 diabetes mellitus on metformin

Abstract: Background: Metformin use is a known cause of B12 deficiency in patients with type 2 DM (T2DM). Diabetic peripheral neuropathy (DPN) often has clinically indistinguishable clinical features of B12 deficiency-induced peripheral neuropathy (PN). Objective: The present study aims to assess serum vitamin B12 levels in patients with T2DM on metformin. Subjects and Methods: This cross-sectional study was conducted at a specialized endocrine outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…The present study found that there was no correlation between serum VitB12 level and the percentage of HbA1c or the age of the participant. These ndings are consistent with several previous studies such as Shahwan et al (2020) [11] , Kim et al (2019) [18] , Alam et al (2021) [30] , Sugawara et al (2020) [32] , and Al Hamdi et al (2020) [31] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study found that there was no correlation between serum VitB12 level and the percentage of HbA1c or the age of the participant. These ndings are consistent with several previous studies such as Shahwan et al (2020) [11] , Kim et al (2019) [18] , Alam et al (2021) [30] , Sugawara et al (2020) [32] , and Al Hamdi et al (2020) [31] .…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the correlation between serum VitB12 level and metformin dose is insigni cant. This result was also showed by Saber et al (2019) [29] , and Alam et al (2021) [30] , but this nding in contrast to ve previous studies reported by Miyan et al (2020) [7] , Al Hamdi et al (2020) [31] , Kim et al (2019) [18] ,…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…D vitamininin de B12 vitamini gibi bipolar affektif bozukluk üzerinde etkisi bilinmesine karşın poliklinik ve kliniklerde bu kan değerlerine bakılmaması nedeniyle yaş, cinsiyet, medeni durum, eğitim durumu, vücut kitle indeksi, ailede psikiyatrik hastalık durumu, alkol kullanımı, sigara kullanımı, madde kullanımı, kan hemoglobin düzeyi, son yatış süresi, kullandığı ilaç türü ve EKT alma durumu arasında herhangi bir ilişki durumu değerlendirilememiştir. Oysa doğru tanı ve tedavi için D vitamini de B12 vitamini gibi bakılması gerekli olan bir kan değeridir (31)(32)(33).…”
Section: Discussionunclassified
“…Metformin-associated B12 deficiency in T2DM was first described in 1969, and since then, many researchers have confirmed the dose-dependent lowering of B12 levels with metformin [ 10 , 11 , 19 ]. Only a few studies have evaluated the changes in vitamin B12 in metformin-treated patients with PCOS, and there is great heterogenicity among the study results.…”
Section: Discussionmentioning
confidence: 99%